2014
DOI: 10.1186/s12881-014-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in DNA repair genes as risk factors associated to prostate cancer progression

Abstract: BackgroundBesides serum levels of PSA, there is a lack of prostate cancer specific biomarkers. It is need to develop new biological markers associated with the tumor behavior which would be valuable to better individualize treatment. The aim of this study was to elucidate the relationship between single nucleotide polymorphisms (SNPs) in genes involved in DNA repair and prostate cancer progression.MethodsA total of 494 prostate cancer patients from a Spanish multicenter study were genotyped for 10 SNPs in XRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The role of 32 SNPs located in 3 key genes involved in testosterone metabolism (SRD5A1, SRD5A2, and CYP17A1) has been explored in a cohort of Spanish patients with PCa, on the assumption that interindividual levels of testosterone and DHT may be influenced by germline polymorphisms in those genes, and this fact could determine clinical characteristics of the tumor, a phenomenon previously observed in relation to SNPs located in genes involved in DNA repair [21].…”
Section: Discussionmentioning
confidence: 98%
“…The role of 32 SNPs located in 3 key genes involved in testosterone metabolism (SRD5A1, SRD5A2, and CYP17A1) has been explored in a cohort of Spanish patients with PCa, on the assumption that interindividual levels of testosterone and DHT may be influenced by germline polymorphisms in those genes, and this fact could determine clinical characteristics of the tumor, a phenomenon previously observed in relation to SNPs located in genes involved in DNA repair [21].…”
Section: Discussionmentioning
confidence: 98%
“…Among the genes analyzed for association between genetic variants and prostate cancer risk or aggressiveness are XRCC1 and XRCC3 (X-ray repair cross-complementing proteins 1 and 3), ERCC1 and ERCC2 (Excision repair cross-complementing rodent repair deficiency, complementation group 1 and 2), LIG4 (Ligase IV), ATM (Ataxia telangiectasia mutated), XPD (Xeroderma pigmentosum group D), MDM2 (Human mouse double-minute 2 protein), CDKN1A, and CDKN1B (Cyclin-Dependent Kinase Inhibitors 1A, and 1B), CCND1 (Cyclin D1) as well as BCL2 (B-cell lymphoma 2) and TP53 (tumor protein p53) [89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Genetic variants within most of these genes were found to be associated with PCa aggressiveness or response to therapy.…”
Section: Dna Repair Cell Cycle Control and Apoptosismentioning
confidence: 99%
“…A recent study conducted in Spain showed the association of rs11615 in ERCC1 and rs17503908 in ATM with PCa aggressiveness [93]. Genetic variants in the same chromosomal region as ERCC1 were previously analyzed in a large study that provided opposing results.…”
Section: Dna Repair Cell Cycle Control and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…(3-7) Furthermore, SNPs in genes responsible for DNA damage repair and cell cycle control may play an important role in affecting cell and tissue response to radiation therapy. (8) Among these, BRCA1 is of particular interest given its major role in DNA damage repair and cell cycle control with possible implications for treatment response in prostate cancer patients receiving radiation therapy. (9-11) Furthermore, our group previously demonstrated that patients with higher tumor BRCA1 protein expression had an increased risk of prostate cancer mortality.…”
Section: Introductionmentioning
confidence: 99%